The Effect of Different Feed Restriction Programs and Dietary L-Carnitine Supplementation on Hepatic Lipogenesis, Plasma Heterophil to Lymphocyte Ratio and Yolk IgY Content of Broiler Breeder Hens - Beer, M. de; Coon, C.N. (International Journal of Poultry Science, 2009)
Two experiments were conducted to determine effects of Everyday (ED) or Skip-a-day (SK) feeding and dietary L-carnitine on lipid metabolism and stress in broiler breeders. In Experiment 1 a 2x2 factorial design was used to compare feeding regimens (ED vs SK) and L-carnitine supplementation (0 vs 50 mg/kg). L-carnitine supplementation began at d 1 and lasted throughout the 45 weeks experimental period. SK programs were implemented from 28 days of age to 5% production. Parameters measured included in vitro Lipogenesis (IVL), Heterophil/Lymphocyte ratio (H/L) and yolk IgY content. Liver and blood samples were taken 1 h after feeding, at various intervals during the rearing and production periods. Both SK feeding and L-carnitine increased liver wts during rearing but differences dissipated after onset of lay. Part of the increase in liver weight in SK birds was due to higher lipid contents. L-carnitine tended to reduce liver lipid during rearing. IVL was increased by SK feeding during the rearing period. L-carnitine and SK feeding interacted to increase IVL at 20, 22 and 27 weeks. H/L was elevated at 7 weeks in SK birds, but no differences were observed after that. Neither L-carnitine nor feeding regimens affected maternal IgY transfer to egg yolks. In Experiment 2, the same effects were tested but a low density grower diet was used from 4-18 weeks. The grower diet had 9% less energy and 7% less protein than in experiment 1. Liver wt was increased in SK and L-carnitine supplemented birds up to 20 weeks. By 40 weeks, ED birds had higher liver weights than SK. Liver fat was generally higher in SK birds than ED during rearing. SK feeding increased IVL but unlike Experiment 1, L-carnitine did not. H/L ratio was elevated in SK up to 20 weeks of age after which no differences occurred. L-carnitine did not affect H/L. In conclusion, feeding regimens and L-carnitine can alter hepatic lipid synthesis. Feeding regimens like SK, incorporating lengthy periods without feed can result in elevated H/L ratios but birds are generally able to adapt to such regimens over time